A NB-IoT access scheme based on Beta distribution - Mengya LI; Zhengquan LI (物联网学报)
As one of the emerging technologies of low-power wide-area Internet of things, narrow band Internet of things (NB-IoT) faces the pressure and challenge of massive connections of terminals.Aiming at practical application scenarios, a preamble allocation scheme based on Beta distribution was proposed.In this scheme, the energy consumption of each time slot device was firstly calculated.The equipment was divided into high energy consumption according to two grouping methods: average energy consumption and cumulative energy consumption.The preamble was assigned to the high-energy-consuming device group first, and the remaining preamble and the conflicting preamble of the high-energy-consuming device group were assigned to the low-energy-consuming device group.The simulation results show that compared with the traditional random allocation scheme, the proposed scheme can effectively improve the average access success rate and average throughput of the NB-IoT system, and can effectively reduce the back off time.